The Work Performance of Married Female Employees during Covid-19 Pandemic - Ian Nurpatria Suryawan; Yohana F. Cahya Palupi Meilani; Fetty Asmaniati; Nurbaeti Nurbaeti; Myrza Rahmanita (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2021)
The research aims to determine the effect of learning organizations on married female permanent employees' performance at restaurants in Jakarta and Bali by mediating job satisfaction and organizational commitment. The phenomenon that occurs is that married female employees at restaurants tend to work less optimally and are reluctant to participate in development training programs since the Covid-19 pandemic in early 2020. This quantitative research was conducted with purposive random sampling on 73 married female employee respondents. The measuring instrument is a questionnaire with five-Likert scales—data processing using CB-SEM with Smart PLS program. The results showed a significant influence of learning organizations on female staff performance through the mediation of job satisfaction and organizational commitment. The research contribution is expected to provide input to the management at restaurants in managing the performance of married female employees.